Penerapan Model Vector Autoregressive (VAR) untuk Memprediksi Harga Cengkeh, Kopra dan Pala di Sulawesi Utara - Yulin Tunang; Tohap Manurung; Nelson Nainggolan (Sam Ratulangi University, 2019)
YULIN TUNANG. Application of Vector Autoregressive (VAR) Model to Predict Prices of Clove, Copra and Nutmeg Commodities in North Sulawesi. Under the guidance of NELSON NAINGGOLAN as main supervisor and TOHAP MANURUNG as a co-supervisor.The purpose of this study is to determine the vector autoregressive (VAR) model of the prices of clove, copra and nutmeg commodities in North Sulawesi. The data used are data on monthly prices of cloves, copra and nutmeg for the period of January 2015 to March 2019. Parameter estimation results for clove prices are estimated parameter values of 0,174; 0,260; 0,151 while for the copra price, the estimated value of the parameter is 0,060; 0,004; 0,002; and for nutmeg prices the parameter value of 0,215 is obtained; 0,105; 0,625. Prediction results for April, May and June 2019, namely in April 2019 the price of cloves was Rp90.882, the price of copra was Rp4.461, and the price of nutmeg was Rp70.316. The prediction results in May 2019 of clove prices amounted to Rp90.231, copra prices amounted to Rp4.411, and nutmeg prices were Rp70.021. Predicted results in June 2019 of clove prices amounted to Rp89.392, copra prices of Rp4.356, and nutmeg prices of Rp69.532. Keywords: Vector Autoregressive (VAR) model, clove, copra, nutmeg.